Does Institutional Setting Contribute to the Public Debt — Income Inequality Relationship in Developing Economies? - V. B. Nguyen (Финансы: теория и практика)
In the context of increasing globalization, income inequality is one severe problem in several countries because it widens the income gap between the rich and the poor, which leads to social instability. Narrowing this gap has become one of the main agendas in many developing countries to satisfy the millennium goals proposed by the United Nations. Meanwhile, government expenditure is one crucial fiscal instrument as it contributes significantly to running the economy and overcoming economic cyclicality. In particular, governance/institutional can positively adjust the public debt — income inequality relationship in developing economies. The purpose of the study to identify the impact of institutional quality, public debt and their interaction on income inequality on a balanced data panel of 34 developing economies for the period 2002–2020. For monitoring endogenous problems and serial autocorrelation in empirical equations, two-step and one-step system GMM (Generalized Method of Moments) assessments are used. The results from the study show that public debt and the quality of institutions increase income inequality, but their interaction narrows it. These results seem to be counter-intuitive. Besides, education enhances income inequality in these economies. The results of the study provide some policy recommendations for reducing the inequalities in society through public debt and the quality of institutions in developing economies. Accordingly, governments in developing economies should use spending financed by public debt to support low-income individuals through social transfers throughout economic development. Importantly, they should spend more on education and health to help the poor improve their skills and knowledge, narrowing the income difference between the rich and the poor. In particular, they should be prudent in controlling and managing public debt to avoid a public debt crisis and social instability.